Understanding gully process in two Kansas landscapes - Burke, Katherine J. (Kansas State University, 2015)
Gullies often form as a result of land use changes and associated factors such as soil compaction, vegetation removal and changes in rainwater infiltration. Gully erosion creates human safety hazards, soil loss, and sediment and nutrient pollution downstream. Across the globe, researchers have found a wide variety of gully growth rates and drivers (Poesen, Nachtergaele, Verstraeten, & Valentin, 2003), but after the late 1900s, very few published gully studies have been done in the United States, and fewer studies have been done in the Midwest and Great Plains regions. This gully study was conducted in two heavily-used Kansas landscapes: Fort Riley military training areas and agricultural fields in McPherson County. The purpose of the study was to quantitatively measure rates and patterns of gully erosion, as well as identify main drivers of gully initiation and growth. Results and conclusions add Kansas gully characteristics to the growing knowledge of gully erosion in other areas of the world. Gullies in both landscapes were surveyed in the field multiple times per year over three consecutive years (2012-2014) to capture patterns and rates of change. Rainfall data and land characteristics such as soils, vegetative cover, slope, and drainage area were compiled into a database to be compared to gully erosion rates in an attempt to correlate gully erosion not only to rainfall but to other land-based factors. Results show that for most Fort Riley gullies, beds are filling and banks are widening, and consistent drivers of erosion could not be determined from the data. In McPherson, gully channels are storing large amounts of sediment, though gully networks in the upper areas of the gully channels are actively widening and advancing headward. Drivers of channel change in McPherson County seem to be related to vegetative cover, slope, and early spring freeze/thaw processes. At both study locations, land use changes related to linear disturbance and reduced vegetative cover are suspected to have more of an influence on gully growth than rainfall events during the study timeframe. Objectives for best management practices are proposed for both Fort Riley and McPherson County.
Keywords: Gully erosion; Soil conservation; Agriculture; Kansas; Fort Riley; Natural Resource Management (0528)